Outcomes in Chest Wall Reconstruction Using Methyl Methacrylate Prostheses: A Review of the Literature and Case Series Utilizing a Novel Approach with Biologic Mesh - Shah, Nikhil R.; Ayyala, Haripriya S.; Tran, Bao Ngoc N.; Therattil, Paul J.; Keith, Jonathan D. (Journal of Reconstructive Microsurgery, 2019)
Background Composite defects after chest wall resection may leave patients at risk with lack of protection of vital structures and potentially respiratory compromise secondary to flail segments. Reconstruction of the chest wall with various alloplastic materials is possible and well described. Here, the authors present a novel technique in chest wall reconstruction utilizing a methyl methacrylate (MMA) “sandwich” with biologic mesh. The authors also sought to determine outcomes in chest wall reconstruction with MMA to optimize surgical decision making and minimize patient morbidity.Methods A literature review was conducted using MEDLINE and the Cochrane Collaboration Library for primary research articles on chest wall reconstruction using MMA. Data related to surgical techniques and patient outcomes were extracted and analyzed. The authors also present their case series and outcomes utilizing a novel technique with biologic mesh.Results Seventy-four articles met inclusion criteria, which included a total of 562 patients. Reconstruction methods included three main variations of the MMA prosthesis and six institution-specific variations. Complications were reported in 13.7% of patients; the most common complications included infection (5.6%), respiratory failure (3.3%), and atelectasis (1.7%). Less commonly reported complications included prosthesis dislocation (1.2%), pneumonia (1.0%), and lung collapse (0.4%). Overall mortality due to respiratory causes was observed in nine patients (1.6%). In our case series, complications included respiratory failure and seroma was reported in one patient, with no complications at long-term follow-up.Conclusion There are a variety of options available for rigid and nonrigid prosthetic repair of the chest wall. We present the first successful reported case series of reconstruction using biologic mesh as a component of the MMA sandwich prosthesis. MMA appears to be a safe and effective choice for rigid reconstruction when used alone or in conjunction with synthetic or biologic mesh.
Keywords: acellular dermal matrix; biologic mesh; chest wall reconstruction; methyl methacrylate; sandwich method; thoracoplasty